Improving Students' Mathematical Representation Skills through a STEM-Integrated Problem-Based Learning (PBL) Model on Inverse Proportionality Material - Mastri Angely Br. Sitanggang; Najwa Azzahra; Sevrianna Simarmata; Tiara Rezeki Simamora; Anisah Larasati; Gavrila Nathania; Kholishoh Humairoh Lubis (Universitas Trunodjoyo Madura, 2026)
This study aims to determine the improvement of students’ mathematical representation ability after the implementation of the STEM-integrated Problem Based Learning (PBL) model on inverse proportion material. This study employed a quantitative approach with a pre-experimental design using the One Group Pretest–Posttest Design. The research subjects consisted of 28 seventh-grade students of Amir Hamzah National Education Junior High School. The research instrument was a descriptive test of mathematical representation ability administered before and after the treatment. The data were analyzed using descriptive statistics, inferential statistics, and N-Gain analysis. The results showed that the average pretest score increased from 9.29 to 28.93 in the posttest after the implementation of the STEM-integrated PBL model. In addition, the average N-Gain score obtained was 0.28, which was categorized as low improvement. The results of the paired sample t-test also indicated a significant difference between students’ pretest and posttest scores after the treatment (p 0.05). These findings indicate that the STEM-integrated PBL model had a positive effect on students’ mathematical representation ability. The improvement was reflected in students’ ability to present mathematical ideas visually, symbolically, and verbally after participating in the learning process. In addition, the STEM-integrated PBL model encouraged students to be more active in discussions, collaboration, and solving contextual problems, making learning more meaningful. Therefore, the STEM-integrated PBL model can be used as an alternative mathematics learning model that is active and student-centered.